(untitled) (Homoeopathy for All, 2024)
Generally, humans shed between 50 and 100 single hairs per day. Hair shedding is part of a natural balance — some hairs fall out while others grow in. An interruption in this balance — when hair falls out and less hair grows in — causes hair loss. The medical term for hair loss is “alopecia.” Hair grows on almost all of your skin surfaces — not the palms of your hands, soles of your feet, lips or eyelids. Light, fine, short hair is called vellus hair. Terminal hair is thicker, darker and longer.